2009
DOI: 10.1002/cne.22156
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional properties of GnRH neuroterminals in the median eminence of young and old rats

Abstract: The decapeptide GnRH that regulates reproduction in all vertebrates is stored in, and secreted from, large dense-core secretory vesicles in nerve terminals in the median eminence. GnRH is released from these terminals with biological rhythms that are critical for the maintenance of normal reproduction. During reproductive aging in female rats, there is a loss of GnRH pulses and a diminution of the GnRH surge. However, information about the specific role of GnRH nerve terminals is lacking, particularly in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…Furthermore, estradiol acts on endothelial cells to induce retraction of tanycyte processes from GnRH neuron terminals (de Seranno et al 2010); similar mechanisms may exist to regulate astrocyte apposition near the somata of these neurons. In this regard, several studies have shown that changes in steroid milieu, and in particular estradiol, alter glial apposition to GnRH neurons in a manner correlated with number of synapses (Baroncini et al 2007;King and Letourneau 1994;Kozlowski and Coates 1985;Meister et al 1988;Prevot et al 1998Prevot et al , 1999Witkin et al 1991Witkin et al , 1995Witkin et al , 1997Xiong et al 1997;Yin et al 2009aYin et al , 2009b. This apposition can change in a diurnal manner consistent with the estradiol-induced changes in GnRH neuron activity (Cashion et al 2003).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, estradiol acts on endothelial cells to induce retraction of tanycyte processes from GnRH neuron terminals (de Seranno et al 2010); similar mechanisms may exist to regulate astrocyte apposition near the somata of these neurons. In this regard, several studies have shown that changes in steroid milieu, and in particular estradiol, alter glial apposition to GnRH neurons in a manner correlated with number of synapses (Baroncini et al 2007;King and Letourneau 1994;Kozlowski and Coates 1985;Meister et al 1988;Prevot et al 1998Prevot et al , 1999Witkin et al 1991Witkin et al , 1995Witkin et al , 1997Xiong et al 1997;Yin et al 2009aYin et al , 2009b. This apposition can change in a diurnal manner consistent with the estradiol-induced changes in GnRH neuron activity (Cashion et al 2003).…”
Section: Discussionmentioning
confidence: 78%
“…Where then is the GnRH neuron axon? It has been shown that the terminal projection zone of GnRH neurons (the median eminence) contain GnRH fibers with secretary endings (Gross, 1976;Lehman et al, 1988;Yin et al, 2009). It is also known that GnRH neurons Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reconstructed GnRH terminals from young (ϳ5 months) and old (ϳ24 months) ovariectomized rats in three dimensions, thereby revealing novel features of these cells and their microenvironment (12). Here, we extended that previous study by using both descriptive and quantitative measures in three age groups (young, middleaged, and old), and two hormone treatments (estradiol or vehicle) at the light and electron microscopic level.…”
mentioning
confidence: 86%